KINERJA KOMISI PEMILIHAN UMUM KOTA MAKASSAR DALAM MELINDUNGI HAK PILIH WARGA DI TENGAH PANDEMI COVID-19 - Sulistyowati, Dyahwanti; Muhammad, Muhammad; Sukri, Sukri; Ariana, Ariana (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2021)
A common problem that is usually found in the election process is updating the voters’ data. It is a very crucial stage because it is related to the citizens' voting rights. This article looks at how the performance of the General Election Commission of Makassar city (KPU Kota Makassar) in protecting citizens' voting rights during COVID-19 crisis. The research used descriptive research with a qualitative approach. The results of the study indicate that the commission had carried out its duties in the process of updating voters’ data. The list of permanent voters for the 2020 in Makassar mayoral election decreased due to the large number of Makassar residents who were not staying in Makassar during the time of matching and research procedure (coklit). However, socialization continued to be organized bot in conventional and a modern platform through social media. In addition, collaboration with the Department of Population and Civil Registration, KPU Kota Makassar managed to update the data. Hence, people who do not have electronic identification card (E-KTP) can used their voting rights.